2017
DOI: 10.3847/1538-4357/aa60bb
|View full text |Cite
|
Sign up to set email alerts
|

A Submillimeter Perspective on the GOODS Fields (SUPER GOODS). I. An Ultradeep SCUBA-2 Survey of the GOODS-N* † ‡ §

Abstract: In this first paper in the SUPER GOODS series on powerfully star-forming galaxies in the two GOODS fields, we present a deep SCUBA-2 survey of the GOODS-N at both 850 and 450 μm (central rms noise of 0.28 mJy and 2.6 mJy, respectively). In the central region, the 850 μm observations cover the GOODS-N to near the confusion limit of ∼1.65 mJy, while over a wider 450 arcmin2 region—well complemented by Herschel far-infrared imaging—they have a median … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
120
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 79 publications
(131 citation statements)
references
References 113 publications
9
120
2
Order By: Relevance
“…Traditionally, the likely counterparts for single-dish submillimeter sources were identified by using indirect tracers of the far-infrared/submillimeter emission, such as the radio, 24 μm, or mid-infrared properties (e.g., Ivison et al 1998;Smail et al 2002;Pope et al 2006;Ivison et al 2007;Barger et al 2012;Michałowski et al 2012;Cowie et al 2017). These properties roughly track the far-infrared luminosity of galaxies, and they have two additional advantages: that observations in these bands are typically at significantly higher angular resolution than the submillimeter, and that the surface densities of sources in these wavebands are relatively low, so that the rate of chance associations is also low.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, the likely counterparts for single-dish submillimeter sources were identified by using indirect tracers of the far-infrared/submillimeter emission, such as the radio, 24 μm, or mid-infrared properties (e.g., Ivison et al 1998;Smail et al 2002;Pope et al 2006;Ivison et al 2007;Barger et al 2012;Michałowski et al 2012;Cowie et al 2017). These properties roughly track the far-infrared luminosity of galaxies, and they have two additional advantages: that observations in these bands are typically at significantly higher angular resolution than the submillimeter, and that the surface densities of sources in these wavebands are relatively low, so that the rate of chance associations is also low.…”
Section: Introductionmentioning
confidence: 99%
“…850 m (mJy), which is more than a factor of two smaller than the conversion (143) found in Cowie et al (2017). However, the median redshifts of the two samples are z = 1.24 (this work) and z = 2.28 (Cowie et al).…”
Section: μM Flux Density To Sfr Conversionmentioning
confidence: 40%
“…Barger et al (2014) and Cowie et al (2017) have both measured the mean conversion between observed 850 μm flux density and IR SFR from their samples, with a multiplicative range over the individual values of two in each direction about the mean. Here we perform the same exercise, comparing our observed 850 μm flux densities and IR SFRs for the 10 sources that have IR SFR measurements in Figure 6.…”
Section: μM Flux Density To Sfr Conversionmentioning
confidence: 99%
See 2 more Smart Citations